2018
DOI: 10.1016/j.chiabu.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Victimization and traumatic stress: Pathways to depressive symptoms among low-income, African-American girls

Abstract: Socioeconomic disadvantage is associated with increased exposure to victimization and traumatic stress. The present study evaluates longitudinal pathways linking victimization and trauma to depressive symptoms in a socioeconomically disadvantaged sample of African-American adolescent girls seeking mental health services (N = 177, 12-16 years old at baseline). Girls completed four assessments over the course of three years (T1-T4). Depressive symptoms were assessed at T1-T3 using clinical interviews and questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
(89 reference statements)
1
5
0
Order By: Relevance
“…The results also revealed that childhood sexual abuse was associated with depression among women but not among men. These are in line with studies that have childhood sexual abuse to have a greater effect on depression for women (Chen et al, 2014; Gershon et al, 2018), although other studies have reported a greater effect of sexual abuse and depression among men (Dinwiddie et al, 2000; Silverman et al, 1996).…”
Section: Discussionsupporting
confidence: 90%
“…The results also revealed that childhood sexual abuse was associated with depression among women but not among men. These are in line with studies that have childhood sexual abuse to have a greater effect on depression for women (Chen et al, 2014; Gershon et al, 2018), although other studies have reported a greater effect of sexual abuse and depression among men (Dinwiddie et al, 2000; Silverman et al, 1996).…”
Section: Discussionsupporting
confidence: 90%
“…Stress was studied in various forms in rodent populations and humans [ 144 , 145 , 155 , 174 , 176 , 180 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 ].…”
Section: Resultsmentioning
confidence: 99%
“…Children raised in poverty are often exposed to chronic stress, either directly (from food, housing, energy insecurity( 220 ), bullying( 221 , 222 ), or neighborhood violence( 126 )) or indirectly via parental stress( 223 ). Higher HCC were associated with lower parental education( 224 ), lower family income, more household members, single-parent households( 201 ), and deprived neighborhoods( 219 ).…”
Section: Cortisol As a Biomarker Of Early Life Adversitymentioning
confidence: 99%